Effect of Macroeconomic Factors on Credit Risk of Banks in Developed and Developing Countries: Dynamic Panel Method - Ghyasi, Azar (International Journal of Economics and Financial Issues, 2016)
Globalization phenomenon provided a suitable environment with new opportunities for investment in various countries. In this way, the issue of credit risk of countries and rankings of international ranking institutions has become more important. Owing to the fact that using values and numbers and quantization of the measured variables in evaluation of the risk of countries is considered as an appropriate tool for analysis of the economic status of each country. In this paper, it is tried to explore the economic conditions and the effect of macroeconomic variables on the credit risk of developed and developing countries. The model presented in this work can help managers of countries in economic and financial decisions of countries to prevent increase in credit risk and improvement of the credit. For this end, 14 countries in developed and developing countries were selected (developing: Iran, Brazil, Turkey, South Africa, china, Russia and India, developed countries: USA, GBK, Germany, France, Japan, Canada, Switzerland). Results of research revealed that credit risk of the past with regression coefficient as much as 1.174 has the highest contribution to the credit risk of the current period. Furthermore, results implied to the positive and significant effect of development on credit risk of countries. Keywords: credit risk, developed and developing countries, panel model JEL Classifications: G, G2, G21